THE STUDENTS’ ANXIETY IN DELIVERING ENGLISH PRESENTATION - Sardian Maharani Asnur (UIN Alauddin Makassar, 2013)
AbstractAnxiety indeed an ordinary thing experienced by everyone when talking in public and can be increased if it is done by using a foreign language. This paper aims to provide a specific description of the students’ anxiety in delivering English presentations as well as provide a solution on how to deal with the anxiety. There are several factors that affect student anxiety, namely internal factors which covers fear of failure, fear of criticism, conflicting emotion, speech anxiety, negative experience, fear of losing the thread of material, fear of being stopped, and negative thinking; and external factors which covers condition of presentation room, failing to practice, gender, and physical factor. Strategies that can be applied by participants to cope their anxiety in delivering English presentation are: (a) to keep thinking positively toward the audience, the speech, and their self as a speaker, to made good preparation, to rehearse, to keep self-confidence, and to do relaxation.AbstrakKecemasan merupakan hal yang lumrah dialami oleh setiap orang pada saat berbicara di depan publik. Kecemasan itu sendiri dapat bertambah jika dilakukan dengan menggunakan bahasa asing.Tulisan ini bertujuan untuk memberikan gambaran khusus mengenai kecemasan siswa dalam membawakan presentasi berbahasa Inggris serta memberikan solusi cara untuk menghadapi kecemasan tersebut. Terdapat beberapa faktor yang mempengaruhi kecemasan siswa yaitu faktor internal yang meliputi takut salah, takut kritikan, konflik emosi, kecemasan berbahasa, pengalaman negatif, takut lupa materi presentasi, takut distop, dan pikiran negatif, dan faktor eksternal yang meliputi kondisi ruangan, gagal berlatih, gender, dan faktor fisik. Adapun strategi yang dapat dilakukan oleh siswa untuk mengatasi kecemasan mereka pada presentasi berbahasa Inggris yaitu, (a) berpikir positif, (b) membuat persiapan yang optimal, (c) berlatih berulang-ulang (d) percaya diri, dan (e) melakukan relaksasi.